2019
DOI: 10.1021/acs.analchem.9b02656
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Reactive Acyl-CoA Species Mediated Protein Acylation by HPLC–MS/MS

Abstract: Recently discovered acylation by reactive acyl-CoA species is considered a novel regulatory mechanism in epigenetics and metabolism. Established analytical methods like Western blotting and proteomics fail to detect the plethora of acylation structures in a single analysis and lack the ability of absolute quantitation. In this paper, we developed an HPLC–MS/MS method for the simultaneous detection and quantitation of 14 acylated lysine species in biological samples. Extensive effort was invested into method va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…N 6 -formyl lysine, N 6 -acetyl lysine, furosine, methionine sulfoxide, methionine sulfone, o-tyrosine, o,o-dityrosine, and citrulline were purchased from Sigma-Aldrich. Synthesis and structure elucidation of commercially unavailable authentic reference standards was described previously 9,13,19,20 . Structural formulas of analytes are included in the supporting information ( Figure S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…N 6 -formyl lysine, N 6 -acetyl lysine, furosine, methionine sulfoxide, methionine sulfone, o-tyrosine, o,o-dityrosine, and citrulline were purchased from Sigma-Aldrich. Synthesis and structure elucidation of commercially unavailable authentic reference standards was described previously 9,13,19,20 . Structural formulas of analytes are included in the supporting information ( Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic hydrolysis. Enzymatic hydrolysis was performed as described previously 20 . A small crystal of thymol was added to aliquots (250 µL) of protein solutions.…”
Section: Extraction Cytosolic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hydrophobic derivatives of lysine acetylation ( Figure 1 ) like aliphatic propionylation and butyrylation ( Chen et al, 2007 ), unsaturated crotonylation and tiglylation ( Tan et al, 2011 ; Baldensperger et al, 2019 ), branched-chain isobutyrylation, 2-methylbutyrylation, and isovalerylation ( Baldensperger et al, 2019 ; Zhu et al, 2021 ), as well as aromatic benzoylation ( Huang et al, 2018 ) have been reported in literature previously. Due to structural similarity, propionylation and butyrylation have effects comparable to acetylation in remodeling chromatin structure and activation of transcription ( Kebede et al, 2017 ).…”
Section: Acylation By Acyl-coa Thioestersmentioning
confidence: 96%
“…Posttranslational modifications (PTMs) of proteins, including acetylation and formylation, are important in regulating biological systems 1,2 . Measuring acetyl and formyl PTMs employs liquid chromatography/tandem mass spectrometry (LC/MS/MS) analysis via a proteomic approach (analyzing peptides), 2,3 or measuring modifications after digesting proteins to single amino acids 4–6 . Measuring N 6 ‐formyl lysine in proteins is of increasing interest because this modified amino acid forms at locations in proteins that interfere with other PTMs (acetylation and methylation).…”
Section: Introductionmentioning
confidence: 99%